Voice rehabilitation with phonatory prosthesis after total laryngectomy and pharyngolaryngectomy: comparison of functional outcomes between primary and secondary puncture - Salvador, Pedro; Guimarães, Joana; Monteiro, Eurico (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Tracheoesophageal puncture (TEP) with voice prosthesis (VP) placement is considered the standard for vocal rehabilitation after total laryngectomy (TL). This study aimed to compare the success rate of primary and secondary TEP and to evaluate the impact of clinical factors on functional outcome. Methods: A retrospective medical chart review was conducted in patients who underwent TL or pharyngolaryngectomy (PLT) and TEP. Variables collected included age, gender, comorbidities, tumor location and stage, extension of surgical resection, reconstruction, neck dissection, radiation therapy, salvage surgery, device lifetime, postoperative complications and successful voice restoration. Results: A total of 186 patients were enrolled in this study, 164 patients (88.2%) underwent primary TEP and 22 (11.8%) secondary TEP. Successful voice rehabilitation was achieved in 76.9% of patients and there was no difference between primary and secondary TEP groups (76.2% vs. 81.8%, p=0.76). A poorer voice restoration outcome was found in patients who underwent radiation therapy (p=0.01) or salvage surgery (p=0.03). Adjuvant radiation was the only independent prognostic factor for functional success (OR=4.7, IC 95%= 1.4-15.9, p=0.04). VP related complications occurred in 65.7% of patients, with higher incidence in secondary TEP group (90.9% vs. 67.7%, p=0.03). Overall device lifetime was similar between primary and secondary groups (9.2 vs. 8.7 months, p=0.89). Conclusions: Voice rehabilitation outcome was similar with primary and secondary TEP. However, TEP related complications were more common in secondary procedures. Primary TEP allows earlier voice restoration, avoiding a second surgical intervention. Functional success rate was poorer for patients who underwent radiation therapy.